2021
DOI: 10.1002/anie.202107181
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Labeling of Legionaminic Acid in Flagellin Glycosylation of Campylobacter jejuni Identifies Maf4 as a Putative Legionaminyl Transferase

Abstract: Campylobacter jejuni is the major human food‐borne pathogen. Its bipolar flagella are heavily O‐glycosylated with microbial sialic acids and essential for its motility and pathogenicity. However, both the glycosylation of flagella and the exact contribution of legionaminic acid (Leg) to flagellar activity is poorly understood. Herein, we report the development of a metabolic labeling method for Leg glycosylation on bacterial flagella with probes based on azide‐modified Leg precursors. The hereby azido‐Leg labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Indeed, a 2021 study by the Wennekes and Wosten groups showed that azide-modified legionaminic acid precursors label flagellin glycoproteins in C. jejuni and enabled the identification of a glycosyltransferase likely to be responsible for legionaminic acid installation into flagellin (see Section 4.1.2). 193 3.2.3. Pseudaminic Acid Precursor Derivatives.…”
Section: Chemical Reporters For Lps O-antigen Polysaccharidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, a 2021 study by the Wennekes and Wosten groups showed that azide-modified legionaminic acid precursors label flagellin glycoproteins in C. jejuni and enabled the identification of a glycosyltransferase likely to be responsible for legionaminic acid installation into flagellin (see Section 4.1.2). 193 3.2.3. Pseudaminic Acid Precursor Derivatives.…”
Section: Chemical Reporters For Lps O-antigen Polysaccharidesmentioning
confidence: 99%
“…202 The designed compounds thus had azidoacetyl groups at either the 2-or 4-position, or both, and were prepared in either nonacetylated or peracetylated form (compounds 79−84, Figure 28). 193 All six compounds were prepared in >10 steps from D-fucose via chemical synthesis, which was highlighted by sequential S N 2 reactions to establish the diamino core structure with proper stereochemistry (not shown). 193 Although lengthy compared to the chemoenzymatic synthesis of the related compound AltNAc4NAz (75, Figure 27A), the chemical synthesis route did exhibit the versatility required to access all six target compounds 79− 84.…”
Section: Chemical Reporters For Flagellin Glycoproteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…2011 ; Tra and Dube 2014 ), for example, bacillosamine in N -linked glycans of C. jejuni , Legionaminic acid (Leg) in Legionella Pneumophilia ( Pons et al. 2014 ) and C. jejuni ( Meng et al 2021 ) and Pseudaminic acid (Pse) in C. jejuni , Pseudomonas aeruginosa , Acinetobacter baumannii and Vibrio vulnificus ( Liu et al. 2009 ; Andolina et al.…”
Section: Chemical Glycobiology Techniques To Study Glycan Mimicrymentioning
confidence: 99%